Low-voltage variable current gain CCII based all-pass/notch filter - Sharma, Susheel; Pal, K.; Rajput, S. S.; Mangotra, L. K.; Jamuar, S. S. (National Institute of Science Communication and Information Resources, 2009)
A second order low-voltage current conveyor type II (CCII) based filter circuit which can realize dual filter functions (all-pass/notch) depending on the current gain of CCII has been presented. The circuit employs equal valued components with all capacitors grounded and is more suitable for chip implementation. The circuit offers high input impedance, low output impedance and employs same type of active devices (CCII+). Theoretical results have been validated by PSpice simulations using 0.5 µm technology parameters at supply voltage of ± 0.75 V.